Influence of microstructural parameters on damping capacity in CuAlBe shape memory alloys - Montecinos Espinoza, Susana de Los Angeles (2015)
The influence of microstructural parameters on damping capacity in beta CuAlBe polycrystalline shape memory alloys was studied in detail by compression tests. For higher maximum stresses, the pseudoelastic strain increases, higher values of dissipated energy are obtained, and the specific damping capacity increases to reach a stable value. As the grain size of the samples increases, the dissipated energy decreases, but higher values of the specific damping capacity are obtained and at lower strains. A similar behavior is observed as the test temperature decreases in the range of 278-340 K. Stress-grain size and stress-temperature diagrams were constructed, indicating the areas where it is possible to obtain the PE effect, and the optimal working zones. A quantification of the dissipated energy and the specific damping capacity as a function of rmax, grain size, and temperature was realized.